OP0021 Draft classification criteria for the anca associated vasculitides. (12th June 2018) - Robson, J.C.; Grayson, P.C.; Ponte, C.; Suppiah, R.; Craven, A.; Khalid, S.; Judge, A.; Hutchings, A.; Gray, D.; Rosa, J.; Barrett, J.; Watts, R.A.; et al.
Abstract : Background: Classification criteria for the ANCA-associated vasculitides (AAVs) were developed in the 1980s prior to the use of ANCA testing and newer imaging techniques. The Diagnostic and Classification of the Systemic Vasculitides (DCVAS) study is an international project to update classification criteria for the systemic vasculitides. Objectives: Development of draft classification criteria for Granulomatosis with Polyangiitis (GPA), Microscopic Polyangiitis (MPA) and Eosinophilic Granulomatosis with Polyangiitis (EGPA). Methods: Three phases: 1) Expert panel review of cases to identify gold standard set of new cases of small vessel vasculitis; 2) Item reduction of >8000 individual DCVAS items using data-driven and consensus methodology; 3) Lasso logistic regression models within each development set comparing each of the AAV types to other small and medium vessel vasculitides. Final criteria derived through clinical consensus, tested in validation set. The classification project has received financial support from the ACR and EULAR. Results: The expert review process approved 2072/2871 (72%) of physician diagnosed DCVAS cases, including [724 GPA, 291 MPA, 226 EGPA, 51 polyarteritis nodose (PAN), 220 other small vessel disease (SVV)]. Data driven and expert consensus resulted in 91 items retained. Draft criteria, and sensitivity and specificity in table 1. Conclusions: Draft classification criteria for GPA, MPA and EGPA have been created which reflect current practice and have good sensitivity and specificity. Acknowledgements: DCVAS sites and expert panel members Disclosure of Interest: None declared